Pelatihan pembuatan SOP Berbasis Google Docs - Harini, Dwi; Nugroho, Arie; Andriyanto, Teguh; Indriati, Rini (Universitas Nusantara PGRI Kediri, 2023)
SMAS Kartenegara Kediri is one of the high school level education unit unfer the auspices of the Ministry of Education and culture. The working mechanism at SMAS Kartanegara Kediri is not get details, it is presented invarious formats and is not clear enough. This has an impact on the non-uniform way of carriying out tasks by eacc implementer, making it difficult to determine or measure their performance. Therefore, to solve existing problems, IT governance is needed for the system that is currently running. His IT governance functions to assess how effective and efficient the system is and to produce output in the form of new SOP wich can be used as a reference based on PermenegPan R&B Nomor 35 tahun 2012 wich contains guideline for preparing standart opeations procedures for government administration. Thus the creation of SOP documents must be implemented immediately in order to improve the quality of performance, both personal and institutional.